حركة العودة إلى المسج د في الموسيقى التصويرية الأصلية لفيلم خمس زوايا المساجد - Nur Hidayah (CMES (Center of Middle Eastern Studies), 2020)
This article discusses the concept of Islamic aesthetics, which is the view of art and beauty according to Ismail Raji Al Faruqi and Seyyed Hossein Nasr, the representation of the two intellectual figures is seen as representing a pattern of religious understanding, especially with regard to the perspective of art objects in Islam. The aim is to explain descriptively the comparative views of the two modern Islamic thinkers and examine how Muslims respond to their thoughts in the Islamic art world today. furthermore, the article explain conceptually how religious art thought is believed and chosen as a basis in determining the direction and expression of art in the socio-cultural space. The method used in this study is descriptive qualitative analytic, with a religious philosophical approach to Islam, while data collection techniques are carried out through qualitatively described literature. The results show that aesthetics built on Sufistic conception and spiritual appreciation so distinctively in it’s paradigm. The Sufistic paradigm emphasizes how art encourages one's psyche without debating legal status, while monotheistic aesthetics built on the basis of dogmatism and belief in the faith underlines the exoteric level, the foundations that are considered permissible or not may not legally Islamic law. Community social responses and the selection of aesthetic views are sectarian in accordance with their religious beliefs.